(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2022)
In this paper we analyze the distribution of energy in the interactive system of the ground-foundation-object for an arbitrary angle of incidence of the seismic wave into the model. The analysis is conducted using a numerical simulation of wave propagation. In our research we use a two-dimensional mathematical model of the system soil-foundation-object. The ultimate goal of the research was to determine how the angle of propagation of the wave affects the amount of seismic energy that enters the object at various stiffness of the foundation, various soil stiffness and the levels of nonlinear response in the soil.